Modified Johnston Failure Criterion from Rock Mechanics to Predict the Ultimate Strength of Fiber Reinforced Polymer (FRP) Confined Columns - Girgin, Zehra Canan (MDPI, 2014)
The failure criteria from rock mechanics, Hoek-Brown and Johnston failure criteria, may be extended and modified to assess the ultimate compressive strength of axially loaded circular fiber reinforced polymer (FRP)-confined concrete columns. In addition to the previously modified Hoek-Brown criterion, in this study, the Johnston failure criterion is extended to scope of FRP-confined concrete, verified with the experimental data and compared with the significant relationships from the current literature. Wide-range compressive strengths from 7 to 108 MPa and high confinement ratios up to 2.0 are used to verify the ultimate strengths in short columns. The results are in good agreement with experimental data for all confinement levels and concrete strengths.
Keywords: confined concrete; fiber-reinforced polymer; axial strength; rock mechanics; Mohr-Coulomb; Hoek-Brown; Johnston; STRESS-STRAIN MODEL; COMPOSITE JACKETED CONCRETE; COMPRESSIVE BEHAVIOR; DESIGN; CYLINDERS; DUCTILITY; Polymer Science